Pembuatan Bibliografi Beranotasi Subjek Kebidanan Koleksi Peprustakaan Politeknik Kesehatan Kementrian Kesehatan Padang - Putri, Meilydia; Marlini, Marlini (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2018)
Abstract The study of this research in about creating a annoted bibliography obstetrics collection subjek in health ministry library of padang is aimed to describe the making of obstertrics annotated bibliography in poltekkes library. This bibliography is use the information references in helping users to find the collection or information needed rapidly and precisely through the inclusion of annotation in this bibliography. This research has been done by a descriptive method by visiting directly to ministry library of padang to observe and do some interviews. After the data analyzed, the conclusion explains some steps of creating a annoted bibliography obstetrics collection subjek in health ministry library of padang: (1) collecting the data; (2)availability of library collection; (3) library material selection ; (4) doing classification; (5)keyword creation; (6) index preparation; (7) typing a bibliographic script, and ; (8) final bibliographic script view.Keywords: creating, bibliographic, and midwifery.